EVALUATION ON ONLINE PLATFORMS IN ENGLISH LANGUAGE TEACHING AT SMP FITRA ABDI PALEMBANG - Vivi Alvionita; Aswadi Jaya; Hermansyah (Universitas PGRI Palembang, 2024)
This study aims to evaluate on online platforms in English language teaching at SMP Fitra Abdi Palembang. The research focused on eighth – grade students at SMP Fitra Abdi Palembang of the 2023/2024 academic year, with the total of 31 students. The researchers using a descriptive qualitative research method that typically involves detailed data to provide a comprehensive understood of a phenomenon. And utilized the data collection techniques with a questionnaire, and interviews. Additionally, the results of the questionnaires showed 3305 of a total score of, indicated that students used online platforms in learned English. In conclusion showed that most eighth – grade students at SMP Fitra Abdi Palembang used the Duolingo app to learned English instead of used Hello Talk app and Beelinguapp.